THE DEVELOPMENT OF NEW TECHNOLOGIES, INTERCULTURAL COMMUNICATION, AND FOREIGN LANGUAGES IN EDUCATION: PERSPECTIVES AND NEW APPROACHES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This article delves into the integration of new technologies, intercultural communication, and foreign language education, offering insights into existing challenges, innovative solutions, and evidence-based recommendations for educators.